BaselMapper: an experimental tool for managing operational risk in banks. (15th September 2011) - Flores, Enrique Bonson; Tomas Escobar; Francisco
The Basel Capital Agreement (Basel II) required all banking entities actively to manage Operational Risk by means of making explicit measurements and creating specific items in their general ledgers. Currently, the most sophisticated resource for handling transactional information is the XBRL-GL Taxonomy, an electronic dictionary of business elements or digital tags based on eXtensible Business Reporting Language (XBRL), the digital mark-up language for financial contexts, which in turn has the special feature of incorporating transactional or Global Ledger (GL) information. This study proposes, in one hand, an extension of that dictionary, to incorporate Operational Risk information, and in the other hand, a simple tool to edit and visualise such reports, called BaselMapper, which is tested with a business expert. Since this experimental tool, BaselMapper, was created in 2007 and validated in 2008, till the publication date of this article, several changes have occurred in both its normative and technical foundations. Due to the financial crisis, the Bank of International Settlements has developed a new set of reforms in banking regulation, beyond the Basel II agreement described here, called Basel III. To consult the current regulatory framework, please visit: http://www.bis.org/bcbs/basel3.htm Operational Risk aspects were not modified. Additionally, a new version of the XBRLGL taxonomy is now available, called Global Ledger, at: http://www.xbrl.org/GLFiles/ that still incorporates the COR-BUS module used here. So, essentially, these changes do not modify the aim of this paper, which is to promote the use of XBRL-enabled technology for Operational Risk measurement in banking institutions at the international level. Further research will be necessary to maintain this tool properly updated, with the substantial participation of more potential users.